2019
DOI: 10.1016/j.heliyon.2019.e01415
|View full text |Cite
|
Sign up to set email alerts
|

SCCmec typing of PVL-positive community-acquired Staphylococcus aureus (CA-MRSA) at a Japanese hospital

Abstract: The epidemiology of Panton-Valentine leukocidin (PVL)-positive MRSA in community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) was examined. Three hundred and forty-two CA-MRSA strains that were susceptible to imipenem and cefazolin were isolated from 1107 samples (intravenous catheter, blood, sputum, urine, skin, wound, and pharynx) from outpatients at Showa University Hospital in Japan between September 2009 and March 2017. The PVL gene was detected in 46 of 342 CA-MRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
0
14
0
3
Order By: Relevance
“…Large-scale analysis of pediatric patients with invasive S. aureus infections recruited from 13 centers in 7 European countries has revealed that overall PVL positivity rate in MRSA isolates in 2016 was 7.8% [21]. On the other hand, reports show that the prevalence of pvl gene among MRSA strains in a Japanese hospital in 2019 was 13.5% [35], whereas PVL-positivity was higher at a rate of 39% among MRSA isolates collected from pediatric patients in China within the same year [36]. Epidemiological surveillance of MRSA strains collected between 2012 and 2017 in Australia showed that 28% of the isolates were PVL positive [37].…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale analysis of pediatric patients with invasive S. aureus infections recruited from 13 centers in 7 European countries has revealed that overall PVL positivity rate in MRSA isolates in 2016 was 7.8% [21]. On the other hand, reports show that the prevalence of pvl gene among MRSA strains in a Japanese hospital in 2019 was 13.5% [35], whereas PVL-positivity was higher at a rate of 39% among MRSA isolates collected from pediatric patients in China within the same year [36]. Epidemiological surveillance of MRSA strains collected between 2012 and 2017 in Australia showed that 28% of the isolates were PVL positive [37].…”
Section: Discussionmentioning
confidence: 99%
“…Quando em contato com as membranas celulares do hospedeiro, reduz a resistência imunológica por lise de leucócitos ou apoptose e tem como alvo os receptores de complemento (GOUDARZI et al, 2019). Em vários estudos, os isolados de S. aureus portadores da toxina PVL estão ligados a infecções cutâneas, incluindo abscessos, furúnculos e feridas cirúrgicas (CHANGCHIEN et al, 2016;FUNAKI et al, 2019;HARCH et al, 2017;IMMERGLUCK et al, 2017;OLANIYI et al, 2018;SHAHINI SHAMS ABADI et al, 2017;SINA et al, 2013). (GOUDARZI et al, 2019).…”
Section: Leucocidina Panton-valentine -Pvlunclassified
“…Quando em contato com as membranas celulares do hospedeiro, reduz a resistência imunológica por lise de leucócitos ou apoptose e tem como alvo os receptores de complemento (GOUDARZI et al, 2019). Em vários estudos, os isolados de S. aureus portadores da toxina PVL estão ligados a infecções cutâneas, incluindo abscessos, furúnculos e feridas cirúrgicas (CHANGCHIEN et al, 2016;FUNAKI et al, 2019;HARCH et al, 2017;IMMERGLUCK et al, 2017;OLANIYI et al, 2018;SHAHINI SHAMS ABADI et al, 2017;SINA et al, 2013 (GOUDARZI et al, 2019). Os isolados de MRSA produtores de toxina PVL podem causar infecções mais graves e complicadas, com maior taxa de mortalidade quando comparadas às cepas que não produzem toxina PVL (ZHANG et al, 2016).…”
Section: Leucocidina Panton-valentine -Pvlunclassified